The association between parental resilience and emotional/behavioural problems in children with autism spectrum disorders: The mediating role of parenting style - Haiyan Wang; Jing Zhao (PLoS ONE, 2026)
Parental psychological resilience plays a crucial role in addressing children's emotional and behavioral problems. However, the association between parental psychological resilience and emotional/behavioral problems of children with Autism Spectrum Disorders (ASD) has been less explored. This study surveyed 258 parents of children with ASD(aged 3–18) who were receiving training at rehabilitation institutions in Shandong Province, China, using questionnaires. Data were analyzed using structural equation modeling to examine the association between parental psychological resilience and emotional/behavioral problems in children with ASD and to identify the underlying pathways. The results indicated that parental psychological resilience is associated with increased prosocial behavior in children with ASD through increased authoritative parenting, while simultaneously being associated with fewer emotional/behavioral problems by reducing permissive and authoritarian parenting styles. This study provides empirical support for family-focused ASD interventions and adds to the growing body of evidence on their effectiveness.